2021
DOI: 10.1111/apt.16296
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: non‐invasive prognostic tests for primary sclerosing cholangitis

Abstract: SummaryBackgroundSeveral prognostic tests for primary sclerosing cholangitis (PSC) have been developed, including biochemical models, elastography and magnetic resonance imaging scores.AimTo conduct a systematic review of non‐invasive prognostic tests for PSC.MethodsA systematic review was conducted from 1987 to 2020 of blood tests, biochemical models, elastography and imaging scores associated with outcomes in PSC.ResultsForty studies of prognostic tests that collectively included 16 094 subjects with PSC wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…It demonstrated that normalization or reduction of ALP was associated with improved transplant-free survival and reduced risk of hepatobiliary cancers. 44 In a prospective observational study, this clinical benefit was only significant if ALP reduction was achieved below 1.5 times upper limit of normal, and not by 40% of baseline serum levels. 45 Serum ALP is currently accepted as a reasonable surrogate endpoint in clinical trials or to assess response to therapy in clinical practice, 8 , 9 but will likely benefit from combination with other exploratory parameters and with defined cut-off values.…”
Section: Serum Biomarkersmentioning
confidence: 96%
See 1 more Smart Citation
“…It demonstrated that normalization or reduction of ALP was associated with improved transplant-free survival and reduced risk of hepatobiliary cancers. 44 In a prospective observational study, this clinical benefit was only significant if ALP reduction was achieved below 1.5 times upper limit of normal, and not by 40% of baseline serum levels. 45 Serum ALP is currently accepted as a reasonable surrogate endpoint in clinical trials or to assess response to therapy in clinical practice, 8 , 9 but will likely benefit from combination with other exploratory parameters and with defined cut-off values.…”
Section: Serum Biomarkersmentioning
confidence: 96%
“…It shown superiority to the Child Pugh scoring system in predicting short-term survival, but its application is fairly limited to cirrhotic patients and only allows for prediction up to 4 years. 44 Other novel scores that have outperformed the MRS in predicting survival include the UK-PSC score, Amsterdam-Oxford model and Primary sclerosing cholangitis Risk Estimate Tool, 44 which should be considered as secondary endpoints in future clinical trials.…”
Section: Prognostic Scoresmentioning
confidence: 99%
“…Prognostic scores were evaluated to assess the clinical courses of PSC and are presented in Table 2. Using the Mayo Risk Score as a parameter of PSC disease progression [21], a significant higher overall score was found in patients with isolated PSC compared to patients with coexisting IBD (2.46 (1.22-3.56) vs. 1.05 (0-2.28), p = 0.015; Table 2). The Amsterdam-Oxford PSC score, Child-Pugh-Score and MELD Score, however, showed no significant differences between the two cohorts (Amsterdam-Oxford-PSC Score: 2.27 (3.11-1.99) vs. 2.16 (1.66-2.97), p = 0.401; Child-Pugh Score: 7 (5-8) vs. 7 (5-8), p = 0.256; Meld-Score: 13 (7-16) vs. 12 (7-16), p = 0.873; Table 2).…”
Section: Change Of Psc Disease Activity Over Timementioning
confidence: 99%
“…[43] Por otro lado, en pacientes con CBP y CEP un umbral de 9,5-10 kPa ha demostrado ser útil para identificar fibrosis avanzada. [44] Sin embargo, las variables de confusión son frecuentes y el número de pacientes limitado en estos estudios. En los pacientes con consumo activo de alcohol la rigidez hepática puede estar sobreestimada por la inflamación por lo que puede ser necesario repetir la ET cuando se considere que la inflamación ha remitido (2-4 semanas de abstinencia o reducción del consumo con mejoría bioquímica).…”
Section: 2¿en Qué Situaciones La Evidencia Actual Con La Et Es Limita...unclassified